Relationship between failure mechanisms with PCBN tool - Fathul Naim, Abdul Jamil (2008)
Tool wear and eventual tool failure is a consequence of all machining operations and has been the subject of investigative research for the better part of the last century. The study of the tool wear is concern because tool wear adversely affects tool life, the quality of the machined surface and its dimensional accuracy, and consequently, the economics of cutting operations. The focus of this project is to study the relationship between failure mechanism of polycrystalline cubic boron nitrides (PCBN) with cutting parameters such as spindle speed, feed rate and depth of cut in the hard turning machining of hardened steel AISI 4340. All the images of tool wear will be taken using Image Analyzer in order to determine the severity of the wear occurred. The result is analyzed by using Design of Experiment (DOE) methodology with STATISTICA software. Lastly, it was also found that flank wear and crater wear is almost occurred in PCBN tool and spindle speed is the most important process variable associated with tool wear followed by feed rate and depth of cut.